Early Initiation of Intermittently Scanned Continuous Glucose Monitoring in a Pediatric Population With Type 1 Diabetes: A Real World Study - Franceschi, Roberto; Cauvin, Vittoria; Stefani, Lorenza; Berchielli, Federica; Soffiati, Massimo; Maines, Evelina (Frontiers in Endocrinology, 2022)
Background: Use of Continuous Glucose Monitoring (CGM) systems early in the course of diabetes has the potential to help glycemic management and to improve quality of life. No previous research has examined these outcomes in children-adolescents with type 1 diabetes (T1D) who use instant scanning CGM (isCGM) starting within the first month after diagnosis. Aim: To evaluate the impact of isCGM early after diabetes diagnosis on metabolic control and quality of life (QoL), comparing a group who use it from the onset with another one who didn’t have the device during the first year. Subjects and methods: Patients who initiated isCGM within 1 month from T1D diagnosis were enrolled in group A; those who didn’t have the device during the first year were considered as control group (group B). HbA1c and total daily insulin were evaluated at 3 (T1), 6 (T2) and 12 (T3) months post-baseline (T0, diabetes onset), QoL after 1 year. In group A, we also recorded isCGM glucose metrics. Results: 85 patients were enrolled in group A and 67 patients in group B. In group A isCGM was well accepted during follow up: no patient dropped out; percentage of time with active sensor was in mean > 87%; number of scans/day remained stable. QoL was higher in group A than in group B in children (p<0.0001) and in parents (p 0.003). Group A presented lower HbA1c during the first year after diagnosis (p<0.001), and this data correlated with GMI, TIR and mean glucose. The mean±SD hypoglycemia duration decreased during follow-up and honeymoon period lasted more in group A than in B (p 0.01). Conclusions: Early use of isCGM, starting within the first month after diagnosis, improves metabolic control and QoL in pediatric patients with T1D.